Logo on MSME Product Packaging as a Means of Advertising to Increase Sales Results - Samsul Bahri; Rohiman, Rohiman (CV. Media Digital Publikasi Indonesia, 2025)
Logo is one of the important elements in a brand's visual identity, especially in the context of MSME product packaging. This study aims to analyse the role of logos on product packaging as a means of visual advertising that has an effect on increasing sales results. The method used is a descriptive quantitative approach with data collection through questionnaires to 100 consumers and interviews with 15 MSME players in the food and beverage sector in the Lampung region. The results showed that 76% of consumers stated that logos influence purchasing decisions, and 82% stated that logos increase trust in products. Most MSMEs that have redesigned their packaging with a professional logo experienced a 20-35% increase in sales. This finding shows that logos on packaging not only serve as an identity, but also as an effective direct promotional medium in strengthening brand awareness and driving sales conversions. This research suggests that MSMEs should prioritise logo design in their marketing strategy as a long-term visual investment that impacts business performance.